Preparation, Characterization and Testing of an Electrochemical Pumping System for Modifying the Nonstoichiometry of Cerium Oxide CeO2-x - Rink, Florian; Justus Liebig University Giessen (My University, 2026)
Cerium oxide is considered a promising catalyst for HCl oxidation reaction. In this context, it has been found that the oxidation state of cerium oxide (CeO2-x, 0 ≤ x ≤ 0.5) influences the corresponding catalytic activity. For a more detailed investigation, however, a system would be desirable that allows the controlled modification of this. In this work, a respective approach is presented. Based on the Pt/YSZ electrode system, an electrochemical pumping system was devised that allows the oxidation state modification of a CeO2-x(111) film. The cerium oxide films were prepared by pulsed laser deposition and characterized by scanning electron microscopy, X-ray diffraction, Raman spectroscopy and X-ray photoelectron spectroscopy. Beyond that, electrochemical measurements were conducted on various (CeO2-x/)Pt/YSZ/Pt systems. Here, impedance spectroscopy, cyclic voltammetry and potentiostatic polarization experiments revealed effects caused by the cerium oxide film, indicating thereby the working principle of the pumping system. Ultimately, the working principle could be proven using an operando setup that allowed X-ray photoelectron spectroscopy measurements at high temperatures and after applying electric potentials. By this, oxidation as well as reduction of the cerium oxide film could be verified.
Präparation, Charakterisierung und Test eines elektrochemischen Pump-Systems zur Modifizierung der Nichtstöchiometrie von Ceroxid CeO2-x
Keywords: ddc:540